Hoe post-modern is postmodernisme? Enkele gedagtes - L F Schulze (Acta Theologica)
It is imperative for the Christian to confront Post-Modernism and try to gauge its meaning(s). The very term Post-Modernism seems to breathe the fresh eschatological air of being 'with it' in a super way - past the modern age and in uncharted waters. Reference to the Sophists and Sceptics of Ancient Greece, however, turns out some striking similarities to Post-Modernism, disclaiming its ultra novelty. Besides, the sophistry of rhetoric, presupposing and simultaneously feeding relativism, is rejected by Paul (1 Cor 1.17), who proclaims the 'grand design' of history (Eph 2-3).